1997
DOI: 10.1677/joe.0.1540167
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone induces protein secretion and morphological changes in astroglial cells with an increase in expression of glial fibrillary acidic protein

Abstract: Thyroid hormone (T3) induces in vitro differentiation of astrocytes from the developing rat brain. T3 treatment induced the appearance of long processes in cultured cerebral hemisphere and mesencephalon astrocytes from embryonic and newborn rats. T3 treatment also produced a change in the morphology of cultured cerebellar astrocytes from 10-day-old rats, but not in cerebellar astrocytes from newborn rats. An increased expression of glial fibrillary acidic protein (GFAP) was also seen in the T3-treated newborn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 18 publications
5
51
0
Order By: Relevance
“…Similar to other neural cells (Walter, 1996;Baas et al, 1997;Lima et al, 1997), purified ameboid microglial cells respond to T3 exposure by increased extension of cell processes, an important step in their acquisition of a ramified phenotype. As for the effect on cell survival, it may be hypothesized that increased or decreased levels of T3 reaching microglial cells contribute to augment or reduce microglial process formation in hyperthyroid and hypothyroid rats, respectively.…”
Section: Pathways For Thyroid Hormone Influences On Microglia: Assessmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar to other neural cells (Walter, 1996;Baas et al, 1997;Lima et al, 1997), purified ameboid microglial cells respond to T3 exposure by increased extension of cell processes, an important step in their acquisition of a ramified phenotype. As for the effect on cell survival, it may be hypothesized that increased or decreased levels of T3 reaching microglial cells contribute to augment or reduce microglial process formation in hyperthyroid and hypothyroid rats, respectively.…”
Section: Pathways For Thyroid Hormone Influences On Microglia: Assessmentioning
confidence: 98%
“…These compounds favor basic processes of neurogenesis, including precursor cell proliferation, neuronal migration, dendritic and axonal growth, myelination, and synaptogenesis (Legrand, 1983;Porterfield and Hendrich, 1993;Bernal and Nunez, 1995). Thyroid hormone also acts as a promoter of astroglial and oligodendroglial differentiation and modulates proliferation of macroglial cells, depending on their stage of maturation and their localization in the brain (Rami and Rabié, 1988;Faivre-Sarrailh et al, 1991;Trentin et al, 1995;Lima et al, 1997Lima et al, , 1998Rodríguez-Peña, 1999).…”
mentioning
confidence: 99%
“…This effect was accompanied by reorganization of GFAP filaments that were spread in the cytoplasm of astrocytes and became organized around the cell nucleus after T 3 treatment (7). In those experiments, we observed that total GFAP expression was not changed (8). Thus, thyroid hormone seems to control many aspects of astrocyte differentiation.…”
Section: T 3 Regulates Protein Expression In C6 Cellsmentioning
confidence: 83%
“…The growth factors secreted by cerebral hemisphere astrocytes promote morphological differentiation in cells derived from cerebral hemispheres of normal and hypothyroid newborn rats. In contrast, the growth factors secreted by cerebellar astrocytes induce proliferation in astrocytes from normal neonatal cerebellum, accompanied by reorganization of glial fibrillary acidic protein (GFAP) filaments without changes in total GFAP amount (6)(7)(8).…”
mentioning
confidence: 99%
“…Moreover, T3 can induce GFAP synthesis and astrocyte differentiation (Lima et al 1997). Oestradiol also promotes differentiation of glial cells with a redistribution of GFAP in hypothalamic astrocytes (Torres-Aleman et al 1992, Mong & Blutstein 2006.…”
Section: Discussionmentioning
confidence: 99%